Student Motivation and Engagement in Blended Learning Environments in Public Schools of Prishtina – Teachers’ and students’ perspectives - Baliu, Era (International Journal of Scientific Research and Management (IJSRM), 2025)
With the rapid advancements in technology, the need for combined teaching, face-to-face instruction with online components, became a priority to ensure that students could continue their education in both these learning environments.  Blended learning has shown positive impacts on student engagement, motivation, and academic performance in various studies.Therefore, this study focuses on students’ motivation and engagement during blended learning. The research was conducted in three different schools in Prishtina and the data was collected through two sets of questionnaires—one for students and one for teachers. The findings of the study were mixed. While some strategies and tools proved effective in fostering student engagement, the results also highlighted challenges in maintaining motivation and active participation in blended learning classroom. Ultimately, the study offers valuable insights into how online education can be structured to better support student learning and engagement in a blended learning environment, especially in younger learners.